2022
DOI: 10.1038/s41598-022-21831-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal nearshore ocean acidification and deoxygenation in the Southern California Bight

Abstract: The California Current System experiences seasonal ocean acidification and hypoxia (OAH) owing to wind-driven upwelling, but little is known about the intensity, frequency, and depth distribution of OAH in the shallow nearshore environment. Here we present observations of OAH and dissolved inorganic carbon and nutrient parameters based on monthly transects from March 2017 to September 2018 extending from the surf zone to the ~ 40 m depth contour in La Jolla, California. Biologically concerning OAH conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…In Southern California, surface waters, down to about 10 m, exceed 20°C in summer months (Southwest Fisheries Science Center, 2023, Clements et al, 2023SOAR Dataset) or during episodic warm water events (Kekuewa et al, 2022). Yet, we found that brown box crabs are unable to survive long at 20°C in the lab but can subsist at 8°C and 15°C for extended periods of at least two months.…”
Section: Thermal Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…In Southern California, surface waters, down to about 10 m, exceed 20°C in summer months (Southwest Fisheries Science Center, 2023, Clements et al, 2023SOAR Dataset) or during episodic warm water events (Kekuewa et al, 2022). Yet, we found that brown box crabs are unable to survive long at 20°C in the lab but can subsist at 8°C and 15°C for extended periods of at least two months.…”
Section: Thermal Ecologymentioning
confidence: 99%
“…In deeper waters off the Southern California coast, brown box crabs are exposed to temperatures averaging 8°C (Southwest Fisheries Science Center, 2023). While brown box crabs are unlikely to experience temperatures above 15°C in the shallower part of their depth range (Donaldson and Byersdorfer, 2005;Southwest Fisheries Science Center, 2023), intertidal and subtidal waters in Southern California can reach temperatures of up to 24°C in the summer or during extreme marine heatwave events that can last for weeks to months (Kekuewa et al, 2022). Little is known about the migration behavior of brown box crabs, but their close relatives, several species of king crabs (Donaldson and Byersdorfer, 2005;Hall and Thatje, 2011), typically reside at depths below 100 m and have been observed migrating to mate and hatch in warmer, shallower waters (0 -100 m) (Stone et al, 1992;Donaldson and Byersdorfer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…DIC ratio), [Ca 2+ ] is the calcium ion concentration, which varies with salinity, and K Ar is the apparent solubility product of aragonite, a function of temperature, salinity, and pressure (Wang et al, 2013;Wanninkhof et al, 2015). Aragonite is prone to dissolve at Ω Ar values lower than one, but calcifying organisms may start experiencing stress under Ω Ar values lower than 2.0 (e.g., Kekuewa et al, 2022;Siedlecki et al, 2021). Quantifying the occurrence of those suboptimal levels (Ω Ar < 2.0) is therefore relevant for the management of shellfish and other important marine resources, such as the oyster Crassotea virginia, an important fishery resource along the northern GoM coast (Turner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Ω Ar represents the solubility of aragonite, a specific mineral phase of CaCO 3 , which can be defined by: ΩAr=[]CO32·0.25em[]Ca2+·0.25emKAr1 ${{\Omega }}_{\text{Ar}}=\left[{{\text{CO}}_{3}}^{2\mbox{--}}\right]\cdot \,\left[{\text{Ca}}^{2+}\right]\cdot \,{{K}_{\text{Ar}}}^{\mbox{--}1}$ where []CO32 $\left[{{\text{CO}}_{3}}^{2\mbox{--}}\right]$ is the carbonate ion concentration, a property strongly correlated to the Alk‐to‐DIC ratio (Alk:DIC ratio), [Ca 2+ ] is the calcium ion concentration, which varies with salinity, and K Ar is the apparent solubility product of aragonite, a function of temperature, salinity, and pressure (Wang et al., 2013; Wanninkhof et al., 2015). Aragonite is prone to dissolve at Ω Ar values lower than one, but calcifying organisms may start experiencing stress under Ω Ar values lower than 2.0 (e.g., Kekuewa et al., 2022; Siedlecki et al., 2021). Quantifying the occurrence of those suboptimal levels (Ω Ar < 2.0) is therefore relevant for the management of shellfish and other important marine resources, such as the oyster Crassotea virginia , an important fishery resource along the northern GoM coast (Turner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Upwelling intensity varies across small spatial and temporal scales and is typically concentrated in the spring and early summer (Hickey, 1979;Marchesiello et al, 2003;Garciá-Reyes and Largier, 2012;Jacox et al, 2018;Cheresh and Fiechter, 2020). During upwelling, minimal values of seasonal dissolved oxygen and carbonate chemistry parameters such as pH are naturally close to biologically significant thresholds, making organisms in the CCS particularly vulnerable to ocean acidification and hypoxia (OAH) events (e.g., Chan et al, 2008;Connolly et al, 2010;Feely et al, 2008;Gruber et al, 2012;Low et al, 2021;Kekuewa et al, 2022). Local adaptation to high environmental variability may provide some ecological resilience (e.g., Sanford and Kelly, 2011;Kelly and Hofmann., 2013;Donham et al, 2023), but widespread die-offs are already a feature of some OAH events (e.g., Grantham et al, 2004;Barton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%